2003
DOI: 10.1080/00016470308540849
|View full text |Cite
|
Sign up to set email alerts
|

Reneration of the donor side after autogenous fibula transplantation in 53 patients

Abstract: We determined the degree of fibular regeneration at the donor site, using radiographs and dual x-ray absorptiometry, in 53 patients who underwent autogenous nonvascularized fibular transplantation for tumor reconstruction in long bones (mean follow-up 15 (3-26) years). Logistic regression was used to determine whether gender, age at transplantation, time since transplantation, bone mineral density (BMD), and length of the graft were associated with fibular regeneration. 26 patients had spontaneous complete bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…There was no restriction of movement of the ankle and knee joints in our study, in accordance with most other studies [18, 19, 25, 26]. …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There was no restriction of movement of the ankle and knee joints in our study, in accordance with most other studies [18, 19, 25, 26]. …”
Section: Discussionsupporting
confidence: 93%
“…Hsu et al and others have also reported on the higher regeneration potential of those of a younger age [26, 31]. The unusual presence of proximal fibula regeneration in a single case in the present study is likely to be due to a favourable balance between interruption of the nutrient artery and the regeneration potential of the vessels and periosteum of a young patient.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…A fibula graft is one of the most common orthopedic procedures for reconstruction of a bone defect, such as after resection of a bone tumor. Reconstruction of the fibula defect after harvesting might not be necessary, because the fibula and interosseous membrane carry only 6% to 16% of the load applied to the lower extremity [10, 11] and spontaneous regeneration of the fibula has been reported previously, especially in children [12]. However, incomplete regeneration or nonunion following fibula harvesting has also been described [1, 13], and the loss of the fibula after its removal sometimes results in significant donor site morbidity, such as surgical scar pain, weaknesses of plantar flexion of the ankle [14], valgus deformity of the ankle [1], ankle instability [15], and tibial fracture [2].…”
Section: Discussionmentioning
confidence: 99%